The court of the caliphate of al-Andalus - Manzano Moreno, Eduardo, 1960- (Edinburgh)
xvii, 462 sayfa
Keywords: “During the second half of the 10th/4th century, the Umayyad caliphate of al-Andalus became a powerful political formation in Western Europe. Described by the contemporary German nun Hrotsvitha as the ‘ornament of the world’, Cordoba was the destiny of embassies and traders coming from places as far away as Constantinople, the Ottoman empire and Italy. The zenith of this political supremacy coincided with the rule of al-Ḥakam II (961-976 CE), whose name is associated with the enlargement of the mosque of Cordoba, the magnificent palatine city of Madīnat al-Zahrāʼ and the rich caliphal library which housed Arab, Latin and Hebrew manuscripts. This book is based on an extraordinary source that had never been the subject of a comprehensive study: the annals written by an official and chronicler of the caliph’s court, ‘Īsà b. Aḥmad al-Rāzī, who carefully annotated the big and small events of the court. Used by Ibn Ḥayyān to compose one of the volumes of his celebrated Muqtabis, these ‘annals’ have come to us in a substantial fragment of more than 135 folia that cover the period from June 971 to July 975 CE. This source provides an eye-witness account of the caliphate, which describes with stunning detail all the events, characters, places and narratives of the Umayyad caliphate, and is a fundamental work in helping us to understand the configuration of the Mediterranean in the 10th century CE.” --